Analisis Filsafat Perenialisme dan Kaitannya dengan Kurikulum Merdeka dalam Pembelajaran Berdiferensiasi - Joni, Yoyon Indra; Harizon, Dian; Susanti, Erlin; Pratiwi, Pratiwi (Journal of Innovation in Teaching and Instructional Media, 2024)
This study aims to examine the relationship between the concept of the Merdeka Curriculum and the philosophy of perennialism, particularly in the context of differentiated learning. The research uses a library research method, with data collection techniques involving literature studies from various relevant sources such as journals, articles, and books. The gathered data is analyzed using content analysis to explore the deep connection between these two concepts. The results indicate that the Merdeka Curriculum aligns with the philosophy of perennialism, which emphasizes the importance of education based on universal and fundamental knowledge. This curriculum prioritizes diverse intrcurricular learning, providing sufficient time for students to delve into concepts and strengthen their competencies. The philosophy of perennialism, which focuses on character development, morality, and true knowledge, also supports the implementation of differentiated learning, which accommodates various learning needs of students. The novelty of this research lies in the integration of these two concepts the Merdeka Curriculum and perennialism into a more inclusive learning context that is relevant to current educational challenges. The contribution of this study offers new insights for educators and policymakers in implementing a more effective Merdeka Curriculum, while also enriching the understanding of the importance of perennialist philosophy in creating learning that focuses on the comprehensive development of students' character and competencies.